Early Maladaptive Schemas and Their Associations with Perceived Parental Bonding among Adolescents Entering Specialized Health Care - Saarijärvi, Pauliina; Salmivalli, Christina; Helmi, Saija; Karukivi, Max (Springer, 2025)
Early maladaptive schemas (EMSs) have scarcely been studied in adolescents. The present study investigates EMSs in two clinical samples of 12-22-year-olds recruited from patients entering a specialized adolescent psychiatry clinic [n = 190] or a pediatric clinic [n = 119] in Finland. The endorsement of EMSs was compared between these samples, and the association of EMSs with perceived parental bonding was assessed. EMSs were assessed with the Young Schema Questionnaire-Short Form 2-Extended and particularly affectionless control parenting style with the Parental Bonding Instrument. The main analyses were conducted using general linear modeling. Significant differences existed between the two samples, with most EMSs and EMS domains being stronger in the adolescent psychiatry sample. The Disconnection and Rejection domain was associated with maternal affectionless control in the adolescent psychiatry sample and paternal affectionless control in the pediatric sample. The results provide novel findings of EMSs in adolescents and their links to parenting.